2022
DOI: 10.1037/hea0001238
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity and adult health: A dyadic analysis of Black American couples.

Abstract: Objective: The association between childhood adversity and adulthood health is well established, but few studies have examined potential effects of childhood adversity on partner health in couples. This study examined the long-term health impact of childhood adversity on individuals as well as their significant others. Method: The participants were 163 distinguishable dyads from the Family and Community Health Study. Health outcomes included both self-reported chronic illness and a messenger RNA index of accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Men’s family-of-origin aggression and men’s childhood family adversity were not significantly related to their partner’s cortisol response during in-lab interactions ( Arbel et al, 2016 ; Kazmierski et al, 2020 ; Winer et al, 2018 ). Another study showed that a person’s adverse childhood experiences was significantly related to their partner’s higher chronic illness and accelerated aging ( Zhang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Men’s family-of-origin aggression and men’s childhood family adversity were not significantly related to their partner’s cortisol response during in-lab interactions ( Arbel et al, 2016 ; Kazmierski et al, 2020 ; Winer et al, 2018 ). Another study showed that a person’s adverse childhood experiences was significantly related to their partner’s higher chronic illness and accelerated aging ( Zhang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…These mixed results on partner’s emotion reactivity, regulation strategies, and stress reactivity using cortisol levels suggest that moderating factors may be at play and explain for whom, for which form of CM, or in which specific context a person’s CM may be related to these outcomes in partners. Moreover, only one study recently examined the association between a person’s CM and their partner’s health reporting associations with their partner’s chronic illness and aging ( Zhang et al, 2022 ). This is an important limitation that underlines the need to conduct more dyadic studies using mixed methods including biological assessment and a diversity of health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation